2021
DOI: 10.3389/fpsyt.2021.712103
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and Life Satisfaction: The Role of the Health-Related Hardiness and Sense of Coherence

Abstract: Introduction: The COVID-19 pandemic is contributing to increased fear and anxiety throughout society, which may affect life satisfaction. Health-related hardiness and sense of coherence (SOC) are personal resources that help people adapt to difficult circumstances. The purpose of this study was to investigate the relationship between fear of COVID-19, SOC, health-related hardiness, and life satisfaction.Methods: A total of 907 Polish people (522 women and 385 men) participated in this study. The Fear of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 78 publications
(118 reference statements)
5
35
0
1
Order By: Relevance
“…The impact of the sense of coherence on coping with stressful situations may be related to the fact that it reduces the experience of negative emotions in difficult situations. The research results confirm that SOC may limit the experience of negative emotions in stressful situations [ 27 ], which may have a beneficial effect on functioning during the disease. Among people with a physical disability after limb amputation or spine surgery, it was found that patients whose sense of coherence level was comparable with the SOC of healthy people did not despair because of their health condition, but they tried to give a new meaning to their lives [ 75 ], which may have a positive effect on health-related quality of life.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The impact of the sense of coherence on coping with stressful situations may be related to the fact that it reduces the experience of negative emotions in difficult situations. The research results confirm that SOC may limit the experience of negative emotions in stressful situations [ 27 ], which may have a beneficial effect on functioning during the disease. Among people with a physical disability after limb amputation or spine surgery, it was found that patients whose sense of coherence level was comparable with the SOC of healthy people did not despair because of their health condition, but they tried to give a new meaning to their lives [ 75 ], which may have a positive effect on health-related quality of life.…”
Section: Discussionsupporting
confidence: 67%
“…SOC seems to be a particularly important variable in the process of coping with multiple sclerosis. The high level of SOC makes it easier to accept the inevitable difficulties [ 27 ]. High SOC is especially necessary for an individual who is affected by strong stressors [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we did not measure many important variables, which could have influenced our results. Since relational and personal resources play a significant role in dealing with pandemic fear [ 55 ], it can be assumed that providing support and care to pregnant women will be a factor that will significantly reduce the fear of childbirth during the COVID-19 pandemic. This limitation should be corrected in future studies on COVID-19 in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Hardiness, defined by Kobasa ( 1979 ) as a personality trait consisting of three fundamental characteristics (commitment, control and challenge), is a protective factor against the negative effects of stress including burnout (White et al, 2020 ; Bartone et al, 2021 ). Several recent studies have also found that this psychological resource is a significant buffer against the adverse psychological effects of stress related to the COVID pandemic, for Health Care and Emergency workers (Maiorano et al, 2020 ; Vagni et al, 2020a ) and also in the general population (Dymecka et al, 2021 ). Furthermore, hardiness is a predictor of adaptive and positive coping (Clarke, 1995 ; Lease, 1999 ; Chan, 2000 ; Bartone and Homish, 2020 ; Kamtsios and Bartone, 2021 ).…”
Section: Introductionmentioning
confidence: 99%